2020
DOI: 10.1210/clinem/dgaa608
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Metastatic Potential in Pheochromocytoma and Paraganglioma: A Comparison of PASS and GAPP Scoring Systems

Abstract: Purpose The Pheochromocytoma of the Adrenal Gland Scaled Score (PASS) and the Grading System for Adrenal Pheochromocytoma and Paraganglioma (GAPP) are scoring systems to predict metastatic potential in pheochromocytoma and paragangliomas (PCC/PGL). The goal of this study is to assess PASS and GAPP as metastatic predictors and to correlate with survival outcomes. Methods The cohort included PCC/PGL with ≥5 years of follow-up o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 29 publications
0
48
0
Order By: Relevance
“…The AJCC commented on the difficulty of reproducing histological grading due to interobserver inconsistency [13,19]. However, GAPP was improved to be more consistent through the use of objective parameters for diagnosis, and the utility was validated by pathologists [20,21]. In addition to our cases, Yu and Wang [2] reported their rectal PGL with lymph node metastasis that was 40 mm in size, and the histological grading by PASS was 6.…”
Section: Factors Predicting Patient Prognosismentioning
confidence: 79%
“…The AJCC commented on the difficulty of reproducing histological grading due to interobserver inconsistency [13,19]. However, GAPP was improved to be more consistent through the use of objective parameters for diagnosis, and the utility was validated by pathologists [20,21]. In addition to our cases, Yu and Wang [2] reported their rectal PGL with lymph node metastasis that was 40 mm in size, and the histological grading by PASS was 6.…”
Section: Factors Predicting Patient Prognosismentioning
confidence: 79%
“…Like the PASS system, the GAPP model also has a high sensitivity (90%) and low specificity [ 58 ]. Wachtel et al [ 85 ] recently published a retrospective cohort study, including 143 subjects with PPGLs about the comparison PASS and GAPP scoring system. They found that a higher GAPP score was associated with metastatic PPGLs, whereas the PASS score was not.…”
Section: Discussion Of the Recommendationsmentioning
confidence: 99%
“…The scheme has been confirmed in several independent series [66][67][68][69][70], but not in other [71,72]. Moreover, in terms of intra-observer variability, the PASS algorithm has been proven subpar-with different pathologists reaching different scores for a considerable proportion of cases [72,73].…”
Section: Pinpointing Metastatic Potential Using Histological Algorithms-is It Possible?mentioning
confidence: 93%
“…Thus, the diverse group of α-KG dependent dioxygenase enzymes (including PHD enzymes targeting the HIF oncoprotein for degradation as well as TET proteins respon-sible for de-methylating the genome) is functional. Upon aberrant TCA cycle regulation (via mutations in genes encoding enzymes catalyzing key steps of the TCA cycle), accumulation of extra-mitochondrial succinate, fumarate and α-KG metabolites will inhibit dioxygenase function, leading to impaired PHD and TET enzyme activity-thereby promoting HIF pathway activation and genomic hypermethylation algorithm has only been reproduced in few independent studies and is still a fairly young study in need of additional verification [72,74,78]. In the meta-analysis discussed above, the GAPP system exhibited a well-trusted "rule-out" function based on the excellent negative predictive value, similarly to what was shown for PASS (Fig.…”
Section: Pinpointing Metastatic Potential Using Histological Algorithms-is It Possible?mentioning
confidence: 99%